Improving adhesion in bonded ceramics through novel additively manufactured surface geometries - Powell, Daniel; Appleby-Thomas, Gareth J.; Painter, Jonathan (Cranfield University Defence and Security, 2024)
Many high-value industries (including medical, aerospace, and defence) utilise ceramics for their favourable properties, such as high hardness, low thermal / electrical conductivity, and chemical resistance. The latter property results from chemical inertness. However, this inertness leads to weaker bond strengths when joining ceramics with other materials, as is often required to overcome their brittle nature and low tensile strength.Geometries can be introduced to the surface of a material to act as adhesion promoters through increasing the surface area of the bond, but more interestingly through mechanical interlocking between the ceramic and bonding material. Whilst this would be impossible to achieve through conventional manufacturing techniques, additive manufacturing (AM) can create these novel surface geometries. This work pushes the capabilities of ceramic AM at a scale of no greater than 500 µm, finding the limits of the current technology. Furthermore, the potential for increased bonding through the generated geometries is investigated.
Keywords: Additive manufacturing; 3D printing; ceramic additive manufacturing; ceramic adhesion; mechanical interlocking